1990
DOI: 10.1111/j.1600-0447.1990.tb05293.x
|View full text |Cite
|
Sign up to set email alerts
|

A controlled dose‐ranging study of remoxipride and haloperidol in schizophrenia ‐ a Canadian multicentre trial

Abstract: The efficacy and side‐effect profile for three dose ranges of remoxipride were compared with haloperidol in 242 schizophrenic inpatients in 13 centres. All patients were in a productive phase of schizophrenia according to DSM‐III criteria. Relative efficacy of low dose (30–90 mg daily) vs middle dose (120–240 mg daily) vs high dose (300–600 mg daily) was compared with the standard dose of haloperidol (15–45 mg daily), as were the side effects. It was concluded that the therapeutic efficacy of remoxipride was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…It is a selective D2-dopamine receptor antagonist [3]. Controlled clinical trials have shown that remoxipride has a good antipsychotic effect, with a significantly lower frequency of extrapyramidal symptoms compared with haloperidol [4,5]. The effect of remoxipride on plasma prolactin elevation is short-lasting [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a selective D2-dopamine receptor antagonist [3]. Controlled clinical trials have shown that remoxipride has a good antipsychotic effect, with a significantly lower frequency of extrapyramidal symptoms compared with haloperidol [4,5]. The effect of remoxipride on plasma prolactin elevation is short-lasting [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…It is a dopamine D2-receptor antagonist having virtually no affinity for muscarinic, adrenergic, histaminergic, serotoninergic or -y-aminobutyric acid (GABA) receptors (Ogren et al, 1984). Controlled clinical trials have shown that remoxipride has an antipsychotic effect, with a significantly lower frequency of extrapyramidal symptoms than haloperidol (Lapierre et al, 1990;Lewander et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Variability of the response can therefore not be attributed to failure of the neuroleptic drug to reach its target. Moreover, much less time is required for occupation of the DA2 receptor (hours) than for expression of the antipsychotic effect (several days or weeks) [43,50]. These data suggest that occupancy of dopamine DA2 receptors is a necessary prerequisite, but by itself not sufficient for expression of the antipsychotic effect.…”
Section: Classical Neurolepticsmentioning
confidence: 86%